Assessment of occupational stress among farmers in Aurangabad district, Maharashtra - Kureshi, Javed Shabbir; Somsundaram, K. V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Since many years Indian farming community, especially farmers from drought prone areas have been under constant occupational stress. This research study was conducted in Aurangabad district of Maharashtra, which has witnessed a sizeable number of farmer’s deaths in recent years, to find out which component of stress was contributing more and affecting the lives of the farmers. Methods: A community based descriptive cross-sectional study was conducted during 2016 in two most affected blocks of Aurangabad where the highest incidence of farmer suicide attempt cases occurred. A stratified random sample of 120 farmers from three strata viz. small, medium and large, from six most affected villages of two Blocks were interviewed with a standard, duly modified, pre-tested farm stress inventory questionnaire which includes questions on various stress related factors such as financial stress, farming hassles, weather stress, work overload and other people as stressor. Results: The results of study revealed that while farming occupation encompasses all types of stresses to farmers, the study area farmers were experiencing unpredictable weather and financial problems as major stress factors. The study also revealed that the differences of stress levels on various factors were statistically significant when compared to size of landholding of the farmers - small farmers were most susceptible. Conclusions: The present study concluded that weather and financial stresses were the most significant as compared to other components of stress for farmers. Weather fluctuations and unpredictability leads to significant effects on the production of crop and which is directly related to the annual income of the farmers, hence policy makers, agricultural scientists, marketing and financial experts create a suitable environment for farmers to overcome these stressors.